Advances in Catalytic Oxidation of Volatile Organic Compounds over Pd-Supported Catalysts: Recent Trends and Challenges - Song, Shengnan; Zhang, Siyuan; Zhang, Xiaolong; Verma, Priyanka; Wen, Meicheng (Frontiers in Materials, 2020)
Volatile organic compounds (VOCs) are toxic and considered as one of the major contributors to the formation of secondary organic aerosols, ozone, and photochemical smog, greatly affecting the human health and environment quality. In order to abate VOCs emission, catalytic oxidation is widely applied in industries and believed to be an efficient and economically feasible way for the elimination of VOCs. This review is mainly focused on summarizing the recent progress and developments in the catalytic oxidation of various VOCs over Pd supported catalysts. Despite their high catalytic performances at much lower temperatures, the wide use of Pd supported catalysts in the industry has been limited by their high cost, low thermal stability, and incomplete oxidation of VOCs. Therefore, the synergistic effect between support and Pd, the reaction conditions, the deactivation mechanism, as well as the strategy to reveal the catalytic oxidation pathway is also systematically summarized. This review aims to give a deep comprehension and guidance for the development of efficient and cost-effective Pd supported catalysts in the near future.